Evaluation NO2 Detection Using Low-Cost Folded-Path Photometer - Januar Arif Fatkhurrahman; Puji Lestari (Directorate for Research and Community Services (LPPM) ITB, 2023)
The measurement of nitrogen dioxide (NO2) in industrial and residential areas needs comprehensive and reliable instrumentation providing long-interference-free operation and minimum maintenance and recalibration. Differential optical absorption spectroscopy can be used as a direct measurement technique based on the specific absorption characteristics of NO2 following the Berr-Lambert law. This paper proposes a low-cost folded-path photometer to measure NO2 in the air. Cheap tubular acrylic was used as a detection cell with a 3D printed framework, making it compact, modular, and flexible. Evaluation of this differential optical absorption spectroscope (DOAS) was conducted by instrument test responses using NO2 gas. The estimated LOD was 1263 ppb using a 2-nm resolution of the spectrometer and a 6-meter detection cell length. Deviation of the DOAS was estimated to be 0.8% at high concentration and 2.85% at low concentration based on the calibrated DOAS. Intercomparison of the results was conducted using two different instruments to evaluate the DOAS’s performance by measuring NO2 from motorcycle emissions, which indicated that there was a good correlation between the results. The coefficient correlation (R) was 0.649 for the DOAS- ASTM D1607 Griesz Saltzmann method pairing and 0.846 for the DOAS- electrochemical gas analyzer pairing.